2016
DOI: 10.1016/j.cegh.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and obesity in early adolescents and its relation to dietary habit and physical activity: A study in Dibrugarh town

Abstract: c l i n i c a l e p i d e m i o l o g y a n d g l o b a l h e a l t h 4 ( 2 0 1 6 ) s 2 2 -s 2 8 a r t i c l e i n f o Article history:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…In similar study, obesity prevalence was found to be significantly higher in children who never consume green vegetables or fruits, daily consume soft drinks, bakery products, chocolate, fried foods. In addition, 26.6% of children were found to be sedentary, and physical activity level was significantly correlated with obesity prevalence (Saikia et al, 2016). Also, the present data were consisted with Garipagaoglu et al, (2008) who confirmed that the obese children consumed less from vegetable-fruit and dairy group as compared to the non-obese children.…”
Section: Results and Discussion: Distribution Of Some Food Items In Nsupporting
confidence: 77%
“…In similar study, obesity prevalence was found to be significantly higher in children who never consume green vegetables or fruits, daily consume soft drinks, bakery products, chocolate, fried foods. In addition, 26.6% of children were found to be sedentary, and physical activity level was significantly correlated with obesity prevalence (Saikia et al, 2016). Also, the present data were consisted with Garipagaoglu et al, (2008) who confirmed that the obese children consumed less from vegetable-fruit and dairy group as compared to the non-obese children.…”
Section: Results and Discussion: Distribution Of Some Food Items In Nsupporting
confidence: 77%
“…Obesity prevalence was found to be significantly higher in children who never consume green vegetables or fruits, daily consume soft drinks, bakery products, chocolate, fried foods. Also 26.6% of children were found to be sedentary, and physical activity level was significantly correlated with obesity prevalence [7].…”
Section: Childhood Obesitymentioning
confidence: 99%
“…Increase in overweight and obesity prevalence among children and adolescents is an important community health problem and it is related to nutritional behavioral factors. [7].…”
Section: Introductionmentioning
confidence: 99%
“…Children and adolescents also experience increasing prevalence in being overweight and becoming obese due to increased dietary intake and physical inactivity [6,7].…”
Section: Introductionmentioning
confidence: 99%